Dari Lembaga Eksekutif ke Komisi Independen: Perkembangan Penuntutan Kejahatan dan Pelajaran dari Indonesia - Bayanullah, Muhammad; Khusaini, Moh.; Madjid, Abdul; Wahyudi, Slamet; Jameelah, Mariyam (Magister of Law, Faculty of Law, University of Mataram, 2025)
This study aims to analyze the impact of political dynamics on institutional independence in criminal prosecution processes, focusing on the Corruption Eradication Commission (KPK) and the National Human Rights Commission (Komnas HAM) in post-1998 democratic transition Indonesia. The central issue examined is how constitutional weaknesses are exploited by lawmakers to manipulate institutional design, thereby undermining the capacity of these bodies to function independently. Utilizing a socio-legal methodology that integrates legal analysis with social science perspectives, this interdisciplinary approach explores the interplay between institutional frameworks, regulatory structures, and political dynamics. The findings reveal that the concept of the unitary executive, previously abandoned, has reemerged as a justification for political intervention in institutional design. Consequently, both the KPK and Komnas HAM have experienced a significant erosion of their institutional independence, impairing their effectiveness in addressing corruption and human rights violations. This study contributes to theoretical debates on institutional challenges in emerging democracies and offers practical insights for safeguarding institutional autonomy to ensure the accountability and integrity of governance structures.